2012
DOI: 10.1357/002224012800502363
|View full text |Cite
|
Sign up to set email alerts
|

Detailed internal wave mixing above a deep-ocean slope

Abstract: Turbulent vertical eddy diffusivity (K z) and dissipation rate (ε) are estimated between 0.5 and 50 m above the sloping side of Great Meteor Seamount, Canary Basin, using 101 moored temperature sensors, 1-mK precision, sampling at 1 Hz. Effectively, detailed observed time-depth temperature images are split in two: a statically stable and a turbulence image. Tides dominate the temperature variations, but the local bottom slope is supercritical to motions at semidiurnal frequencies. Averaged over a fortnight, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
64
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 30 publications
19
64
1
Order By: Relevance
“…A similar result is obtained after comparison of the turbulent part of the observed bottom pressure, p IWTT , with pressure independently estimated from dissipation rates using high-resolution temperature data between 0.5 and 50 m above the bottom (for the method, see van Haren & Gostiaux (2012a)). Under the assumption of isotropic turbulence and high-Reynolds-number flows, Kolmogorov scaling yields at wavenumber k for the, presumably free stream rather than bottom or wall, pressure spectrum (Tsuji & Ishihara 2003) , and U and L the velocity and length scales of the flow.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…A similar result is obtained after comparison of the turbulent part of the observed bottom pressure, p IWTT , with pressure independently estimated from dissipation rates using high-resolution temperature data between 0.5 and 50 m above the bottom (for the method, see van Haren & Gostiaux (2012a)). Under the assumption of isotropic turbulence and high-Reynolds-number flows, Kolmogorov scaling yields at wavenumber k for the, presumably free stream rather than bottom or wall, pressure spectrum (Tsuji & Ishihara 2003) , and U and L the velocity and length scales of the flow.…”
Section: Discussionsupporting
confidence: 68%
“…Van Haren & Gostiaux (2012a) demonstrate that the spectrum of heat flux transits from the canonical internal wave −2 slope to the turbulence −5/3 slope at the frequency where the eddy diffusivity and the pressure spectra transit from their IWC slope to the IWT bulge. Furthermore, the spectral shape of variance and particular time series of intermittent turbulence pressure and vertical currents resemble turbulence observations in the atmospheric boundary layer.…”
Section: Discussionmentioning
confidence: 80%
“…Efforts over the Mid-Atlantic Ridge (Polzin et al 1997) and Hawaii (Klymak et al 2006) have demonstrated increased dissipation over deep, rough topography. Similar observations have been made elsewhere in a growing body of literature (e.g., Gemmrich and van Haren 2002;Nash et al 2007;Alford et al 2011Alford et al , 2014van Haren and Gostiaux 2012). Progress has also been made in predicting the dissipation observed near topography.…”
Section: Introductionsupporting
confidence: 78%
“…Progress has also been made in predicting the dissipation observed near topography. For topography with characteristic slopes that are less steep than internal tide beams, a priori estimates of the expected dissipation are possible from linear models of the generation (St. Laurent et al 2002;Polzin 2009). A fraction of the upward-radiating energy is assumed to dissipate because of wave-wave interactions.…”
Section: Introductionmentioning
confidence: 99%
“…10 When many are used, say 100 at 1 m intervals, time-depth images can be obtained that resolve internal waves and the larger, most energetic turbulence scales, provided the sensors' noise level and precision are sufficiently small (typically 0.001 • C or less). The advantage of measuring temperature over even better spatially resolving acoustics is that the former can quantify the associated turbulence, 11 whereas the latter can only provide qualitative, quasi-synoptic images due to calibration problems. (Nonetheless, such shipborne acoustic images demonstrate very detailed overturning including secondary turbulence along the rim of the largest Kelvin-Helmholtz overturn in high Reynolds number flows in shallow seas).…”
Section: Introductionmentioning
confidence: 99%